3D hierarchical porous carbon foams as high‐performance free‐standing anodes for microbial fuel cells. Issue 1 (6th September 2022) - Li, Huidong; Zhang, Lu; Wang, Ruiwen; Sun, Jinzhi; Qiu, Yunfeng; Liu, Shaoqin
Abstract: Microbial fuel cells (MFCs) that can directly convert chemical energy of organic matter into electrical energy are expected to continuously obtain energy from wastewater. However, the practical application of MFCs is still limited by unsatisfactorily low power output due to low bacterial loading capacity and relatively poor extracellular electron transport (EET) efficiency between anode and electrochemically active biofilm. Herein, hierarchical porous carbon foams (HPCFs) prepared by pyrolyzing nanoscale Fe‐MIL‐88B‐NH2 modified seitan composite were developed as 3D free‐standing MFC anodes. Its marcoporous structure and good biocompatibility favor the bacterial adhesion, while the N‐doped carbon skeleton, abundant mesopores and iron ions boost the bacteria‐electrode charge transfer efficiency. As a result, the HPCF anodes equipped MFCs deliver a maximum power density of 11.21 W m −3 and a current density of 23.11 A m −3, outperforming the most previously reported 3D porous anodes. This study provides a new idea for the design of anodes for high‐performance MFCs. Abstract : The iron‐based MOF nanoparticles/seitan derived hierarchical porous carbon foams (HPCF) provide marcopores for exoelectrogens enrichment and growth, as well as mesopores with N heteroatoms and iron ions for promoting extracellular electron transfer mainly via bound flavin pathway. MFCs equipped by HPCF anode achieve a power density of 11.21 W m −3 and a COD removal speed of 493 mg L −1 d −1 .